“Blood lead level among battery factory workers in low and middle-income countries: Systematic review and meta-analysis” - Olana, Ararso Tafese; Kumie, Abera; Abegaz, Teferi (Frontiers in Public Health, 2022)
Introduction Lead is one of the most health-hazardous causes of acute and chronic poisoning at workplaces. A limited study was conducted on the blood lead concentration among battery factory workers in low and middle-income countries. Therefore, this study will improve workplace health and safety conditions of workers in this sector and serve as baseline data for further studies in this segment of the working setup. Objective This review aims to identify the pooled mean blood lead level among battery factory workers in low and middle-income countries. Methods The search methods considered the following electronic bibliographic databases: google scholar, PubMed, and other gray literature. A funnel plot and Begg test were used to see the publication bias. The heterogeneity of studies was checked using I-square statistics with a cut of point 75% and the Joanna Briggs Institute (JBI) quality assessment tool was applied to ensure the quality of the included articles. A random-effect model was applied to pool the blood lead level intoxication. The sub-group analysis and Meta-regression analysis were conducted by country and year of publication to control heterogeneity and to show variation. We included the articles published from 2000 to 2021 year in the English language. Results Through the search strategies, 135 articles were identified and 43 full-text articles were selected for evaluation, and finally, eighteen (18) articles fit the inclusion criteria. From the 18 studies included in the meta-analysis, the mean pooled blood lead level of workers was 37.996 μg/dl (95% CI: 30.680–45.312) which is higher than the threshold limit value set by American conference of governmental industrial hygienists (20 μg/dl). In subgroup analysis by year in the random effect model, the pooled mean of blood lead level from 2006 to 2011= 43.20 μg/dL (35.91–50.50), 2012–2015 = 37.78 μg/dl (25.23–50.29), and 2016–2020 = 36.53 μg/dl (19.44–53.62). Conclusions This review showed that the pooled mean blood lead level of workers exposed to lead battery factories was (37.996 μg/dl) which is above the threshold limit value (20 μg/dl). Therefore, attention should be given by employers, government, and researchers to improve the health of working populations exposed to lead exposure in low and middle-income countries through the provision of occupational health and safety services like periodical medical checkups, treatments, and provision of training and adequate and appropriate personal protective equipment. Systematic review registration: Identifier: CRD42022322827.